Reflective writing and the self-perceived development of intrapersonal communication skills among first-year university students in the UAE. Issue 1 (2nd January 2022) - Deveci, Tanju; Wyatt, Mark
ABSTRACT: Intrapersonal communication (IC) is inescapable; we constantly engage in self-talk. IC is surprisingly under-researched, but its quality affects students' reflective skills, impacting their academic success. This implies that students' IC skills need to be developed systematically. Our small-scale qualitative study explores first-year university students' self-perceived development of IC skills in the context of a communication course that supported intensive reflective writing experience, with data collected through reflective essays. Results suggest that the students' reflective writing experience impacted their self-perceived IC skills by enhancing analytical and problem-solving processes, self-awareness, positive thinking, and self-esteem, and also supported interpersonal communication skills' development. Introducing first-year university students to reflective writing would therefore seem to be beneficial. However, to generate positive experiences, reflective writing needs to be scaffolded carefully.